Characterization of direct coal liquefaction catalysts by their sulfidation behavior and tetralin dehydrogenation activity. Issue 4 (August 2019) - Chen, Zezhou; Xie, Jing; Liu, Qingya; Wang, Hongxue; Gao, Shansong; Shi, Lei; Liu, Zhenyu
Abstract: Direct coal liquefaction (DCL) involves complex catalytic reactions and catalyst transformation. These catalyst behaviors are not well revealed and correlated with the DCL results in the past due to large errors in conventional high-pressure autoclave experiments, which are slow in heating rate and complex in product separation and quantification. To better understand transformation of DCL catalysts and evaluate their activity, this paper studies activity of seven DCL catalysts in dehydrogenation of tetrahydronaphthalene (THN or tetralin) using a high throughput method and compare the results with the catalytic activity in DCL in a conventional high-pressure autoclave. The catalysts' activities in THN dehydrogenation and in DCL are correlated with their sulfidation behaviors observed in temperature-programmed heating in a 5%H2 S/H2 atmosphere. It is found that the catalysts show the same activity order in THN dehydrogenation and in DCL. The rate constant of THN dehydrogenation and coal conversion and oil yield in DCL correlate well with S content of the catalysts at reaction conditions. Regardless of the metal forms and the catalysts' preparation methods, linear trends are observed: the higher the catalysts' S content, the lower the activation energy for THN dehydrogenation, and the higher the coal conversion and oil yield in DCL. This finding provides a general role as well as easy methods for assessing the catalysts' activity in the direct coal liquefaction, i.e. the catalysts' DCL activity can be evaluated by their S contents or by their activities in THN dehydrogenation. Highlights: Fe, Co and Mo sulfides show the same activity order in DCL and THN dehydrogenation. Catalyst activity directly correlates with its S content at reaction condition. Coal conversion and oil yield linearly proportionate to the catalysts' S content. E a of THN dehydrogenation inversely proportionates to the catalysts' S content. Sulfidation behavior of various catalysts partially correlates with their activity.